2017
DOI: 10.1111/ele.12776
|View full text |Cite
|
Sign up to set email alerts
|

Infection of the fittest: devil facial tumour disease has greatest effect on individuals with highest reproductive output

Abstract: Emerging infectious diseases rarely affect all members of a population equally and determining how individuals' susceptibility to infection is related to other components of their fitness is critical to understanding disease impacts at a population level and for predicting evolutionary trajectories. We introduce a novel state-space model framework to investigate survival and fecundity of Tasmanian devils (Sarcophilus harrisii) affected by a transmissible cancer, devil facial tumour disease. We show that those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
68
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 39 publications
9
68
0
Order By: Relevance
“…Prior work showed a rapid evolutionary response in two small genomic regions on chromosomes 3 and 4 in genes associated with cell‐cycle regulation, cell adhesion and immune response (Epstein et al., ), but the relationship of these genomic regions to specific phenotypes was unknown. Consistent with this previous work, we found that loci involved with immunity, cell‐cycle regulation and cell adhesion underlay variation in female survival and may thereby drive cancer resistance (or tolerance; Wells et al., ). For example, Epstein et al.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Prior work showed a rapid evolutionary response in two small genomic regions on chromosomes 3 and 4 in genes associated with cell‐cycle regulation, cell adhesion and immune response (Epstein et al., ), but the relationship of these genomic regions to specific phenotypes was unknown. Consistent with this previous work, we found that loci involved with immunity, cell‐cycle regulation and cell adhesion underlay variation in female survival and may thereby drive cancer resistance (or tolerance; Wells et al., ). For example, Epstein et al.…”
Section: Discussionsupporting
confidence: 91%
“…Because observing the endpoint of death in a mark–recapture trapping framework is impossible (i.e., cannot trap a dead individual), we estimated survival as the difference in days between the first time an individual was observed with DFTD and the last time it was observed at all; we required at least two capture events following infection and that the individual must have survived ≥40 days to allow for recapture to be possible. We recognize that our survival estimate was a simplified proxy for true survival, but we did not possess the necessary longitudinal data across all sampled sites to more robustly model true survival as previously described (Wells et al., ). Mark–recapture frameworks estimate survival for classes of individuals (e.g., McDonald, ), but individual phenotype estimates are required for GWASes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results support the idea that the frequency of encounter in young devils increases as they breed younger (McCallum et al., ) and therefore increases their chances of contracting DFTD. In addition, there may be less social inhibitions on interactions in long‐term diseased sites with fewer, potentially socially dominant, older devils around (Hamede, McCallum, & Jones, ; Wells et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…This, added to the observation that the disease has been in all but rare cases fatal within 6 months of the appearance of visible symptoms (cf. Hawkins et al., ; Wells et al., ), and that it can reach 100% prevalence in devils 2 years and older (Lachish et al., ; McCallum et al., ), indicates DFTD is a frequency dependent disease with high mortality and infection rates. Indeed, early epidemiological models predicted a high chance of localized extinctions within 25–30 years of DFTD emergence (McCallum et al., ) and were important justification of recovery actions which included captive breeding (Lees & Andrew, ), work towards development of an immunotherapy (Kreiss, Brown, Tovar, Lyons, & Woods, ), and establishment of disease‐free wild sites (Department of Primary Industries Parks Water and Environment, , ).…”
Section: Introductionmentioning
confidence: 99%